2004
DOI: 10.1108/01439910410541837
|View full text |Cite
|
Sign up to set email alerts
|

Laser processing of plastics

Abstract: This paper focuses on some of the presentations given at a technical workshop on “Laser processing of polymer‐based materials”, organised by Association of Industrial Laser Users. Applications in cutting and welding are discussed and specifically how different combinations of polymer materials and laser types produce different results. Applications are described that include pre‐weakening of car trims for integrated airbags and “on the fly” scribing of web materials used in packaging. In several of these appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…There are thermoplastics, such as polyethylene (PE), polycarbonate (PC), polymethylmethacrylate (PMMA) (acrylic), polyvinylchloride (PVC) and thermoset plastics, which include epoxy and phenolic resins (John, 1998;Rooks, 2004). Several authors (Rooks, 2004;Caiazzo et al, 2005;Zhou and Mahdavian, 2004;Mathew et al, 1999;Lum et al, 2000), when reporting on laser cutting of polymeric materials, have shown that the processing parameters have an essential role on the quality of the surface obtained. Caiazzo et al (2005) investigated the CO 2 laser cutting of polymeric materials, specifically applied to polyethylene (PE), polypropylene (PP) and polycar- * Corresponding author.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are thermoplastics, such as polyethylene (PE), polycarbonate (PC), polymethylmethacrylate (PMMA) (acrylic), polyvinylchloride (PVC) and thermoset plastics, which include epoxy and phenolic resins (John, 1998;Rooks, 2004). Several authors (Rooks, 2004;Caiazzo et al, 2005;Zhou and Mahdavian, 2004;Mathew et al, 1999;Lum et al, 2000), when reporting on laser cutting of polymeric materials, have shown that the processing parameters have an essential role on the quality of the surface obtained. Caiazzo et al (2005) investigated the CO 2 laser cutting of polymeric materials, specifically applied to polyethylene (PE), polypropylene (PP) and polycar- * Corresponding author.…”
Section: Introductionmentioning
confidence: 96%
“…According these authors striation patterning is evident but is of little significance to the overall quality of cut as evidenced by the low roughness values obtained. Rooks (2004) reported applications in laser cutting and specifically showed how different combinations of polymeric materials and laser types produce different results. Applications are described that include pre-weakening of cars trims for integrated airbags and "on the fly" scribing of web materials used in packaging.…”
Section: Introductionmentioning
confidence: 97%
“…The major methods used for coated fabrics are mechanical (such as dies or reciprocating knife cutters) and for uncoated fabrics are based on the use of lasers [176][177][178][179][180]. In the former case, the fraying of the edges is prevented by the coating, and in the latter case the heat generated by laser seals the cut edges [181].…”
mentioning
confidence: 99%
“…There are thermoplastics, such as polyethylene (PE), polycarbonate (PC), polymethylmethacrylate (PMMA) (acrylic), polyvinylchloride (PVC) and thermoset plastics, which include epoxy and phenolic resins. Rooks [4], Caiazzo et al [5], Zhou and Mahdavian [6], Mathew et al [7] and Lum et al [8], when reporting on the laser cutting of polymeric materials, have shown that the processing parameters have an essential role on the quality of the surface obtained. Lum et al [8] presented a study about the CO2 laser cutting of medium-density fibreboard (MDF).…”
Section: Introductionmentioning
confidence: 99%
“…According to Powell [3] and Rooks [4], applications of laser cutting in polymeric materials have grown considerably in many industries. Polymeric materials generally fall into main groups.…”
Section: Introductionmentioning
confidence: 99%